Precision pulse capsulotomy complicated by radial tear of the anterior capsule: a proposed mechanism. Issue 11 (November 2019) - Safuri, Shadi; Duvdevan, Nitsan; Socea, Sergiu; Blumenthal, Eytan Z.
Abstract : N/A: Zepto precision pulsed capsulotomy is an emerging technology aimed at providing a safer and more reproducible anterior capsulorhexis, with potential advantages in challenging cases. Initial reports suggest high safety, and thus far to our knowledge, no complications have been reported. Herein we report an unexpected complication. After the pulse delivery phase on a routine cataract case, a radial tear of the anterior capsule was observed. Upon careful review of the surgery video, an air bubble was noted, at the precise clock hour of the radial tear, trapped between the device wire and capsule. This air bubble presumably prevented the transfer of rapid phase transition at this site, interfering with capsule cleavage, and resulting in incomplete capsulotomy. Based on this observation, if a trapped air bubble is observed after the vacuum phase, we recommend applying more vacuum or disengaging and reattaching, before proceeding to the pulse delivery stage.